2015
DOI: 10.1097/tp.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Killer Cells in Humoral Rejection

Abstract: Antibody-mediated rejection (AMR) has been identified among the most important factors limiting long-term outcome in cardiac and renal transplantation. Therapeutic management remains challenging and the development of effective treatment modalities is hampered by insufficient understanding of the underlying pathophysiology. However, recent findings indicate that in addition to AMR-triggered activation of the classical complement pathway, antibody-dependent cellular cytotoxicity by innate immune cell subsets al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 91 publications
2
25
0
Order By: Relevance
“…In addition to the CDC pathway, the NK cell-mediated ADCC is another risk factor for chronic cardiac graft rejection213637. NK cell cytotoxic function occurs through natural cytotoxicity or ADCC38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the CDC pathway, the NK cell-mediated ADCC is another risk factor for chronic cardiac graft rejection213637. NK cell cytotoxic function occurs through natural cytotoxicity or ADCC38.…”
Section: Discussionmentioning
confidence: 99%
“…They bind and activate the complement through the Fc region, which results in complement-dependent cytotoxicity (CDC) and incites the acute antibody-mediated rejection1920. HLA antibodies also activate antibody-dependent cell-mediated cytotoxicity (ADCC) through their Fc region engaging receptors on innate immune cells such as natural killer (NK) cells21.…”
mentioning
confidence: 99%
“…Antibody dependent cell mediated cytotoxicity (ADCC) occurs when the Fc portion of a DSA bound to the transplant endothelium interacts with the Fc receptor on a leucocyte, usually a natural killer cell. This results in the formation of an intercellular synapse that allows the natural killer cell to induce apoptosis of the associated graft endothelium and stimulate the secretion of cytokines which recruit other inflammatory cells to the site . Microvascular inflammation which occurs in the presence of DSA, but in the absence of C4d positivity, may be driven by this manifestation of DSA .…”
Section: Manifestations Of Dsa In the Allograftmentioning
confidence: 99%
“…Direct evidence for the role of NK cells in microcirculation injury during ABMR comes from the findings of NK cells and NK cell transcripts in kidney biopsies from patients with donor-specific HLA antibodies (23, 24). Mechanistic studies confirming the role of DSA-dependent NK cell-mediated cytotoxicity in organ allograft rejections is lacking (25). However, clinical trials with cancer therapeutic antibodies have shown that the induction of NK cell-mediated ADCC have direct bearing on organ allograft rejection.…”
Section: Mechanisms Involved In Antibody-mediated Rejection Of Organ mentioning
confidence: 99%